Assessment of the financial stability of the results of the organization of Sevastopol - L. I. Sachenok (Вестник университета)
The assessment of economic stability and solvency is the main element of the analysis of the financial condition necessary for control, allowing to assess the risk of breach of obligations under the calculations of the enterprise. The purpose of the study was to assess the economic stability of the organization and develop measures to improve it in a market economy. The subject was the study of the financial condition of the organization in the aspect of economic stability. The paper evaluates the results of the economic activities of the micro-enterprise LLC “Solveks Group”. The author gives the characteristics of the organization, investigates the reporting indicators to identify errors in enterprise management. The enterprise was unprofitable for a long time, but recently began to make a profit. It became necessary to determine whether this trend is really positive, or whether it hides new problems. The study carries out an analysis of the liquidity and solvency of the organization, during which identifies a number of problems. The author makes recommendations for improving financial stability.